Exploring the infection strategy of Colletotrichum fructicola in pecan and two effectors Cf-ID1 and Cf-ID2 were characterized using unique molecular identifier-RNA sequencing technology - Hu, Long-Jiao; Xuan, Ji-Ping; Li, Yang; Zhai, Min; Wang, Guo-Ming; Deng, Li-Na; Mo, Zheng-Hai (Frontiers in Plant Science, 2025)
The anthracnose disease caused by Colletotrichum fructicola has widely occurred in pecan (Carya illinoinensis) in China, seriously affecting its fruit yield and quality. However, the details of the infection strategy of C. fructicola remain to be elucidated. In this study, unique molecular identifier-RNA sequencing (UMI RNA-seq) was used to analyze differentially expressed genes (DEGs) of C. fructicola and candidate effectors were predicted. Two candidate effectors were identified during the early infection stages of C. fructicola. There were 6,822 DEGs at three infection timepoints (6, 24, and 36 h post-inoculation), and these genes were involved in spore germination, nutrient uptake, detoxification, secretion of toxic substances (such as effectors and toxins), inhibition of the host’s immune response, and protein post-translational modification, which participated in the pathogenic process of C. fructicola. Moreover, 191 candidate effectors were predicted and their expression trends were divided into five clusters. Two candidate effectors Cf-ID1 and Cf-ID2 were selected for functional validation, and they were demonstrated to trigger cell death and immune response in Nicotiana benthamiana. Cf-ID1 and Cf-ID2 are located in both cytoplasm and nucleus and could suppress the infection of C. fructicola by eliciting defense responses in N. benthamiana. This study provided valuable information for in-depth research on the pathogenesis of C. fructicola.